Pengaruh Influencer Marketing Dan Online Customer Review Padakeputusan Pembelian Dengan Minat Beli Sebagai Variabel Mediasi Pada Pelanggan Platform Tiktok Shop Di Kota Yogyakarta - Pratama, Muhammad Erdin Huda; Lukitaningsih, Ambar; Maharani, Bernadetta Diansepti (Universitas Muhammadiyah Pontianak, 2026)
As PT XYZ's training center aligns its services with corporate strategy and values, it aims to optimize employee performance through effective learning. In support of the company’s cost-efficiency strategy, the center initiates a digital transformation by implementing electronic certificates (e-certificates) to reduce both time and financial costs. This study analyzes risks associated with the implementation of e-certificates, focusing on issuance, authentication, document validity, and system security. The objective is to identify risks related to applications, processes, and documents, and provide mitigation strategies. The final outcome of this research is a set of recommendations to address and minimize identified risks effectively.